A rare presentation of type 2 hyper IgM syndrome in a 17-year-old male: a case report and literature review - Özdemir, Öner; Kılınçkaya, Lütfi; Önata, Ece Tüsüz; Yousef, Ali; Rahmani, Raziq (Alergologia Polska - Polish Journal of Allergology, 2026)
Hyper IgM syndrome (HIGM) is a heterogeneous group of primary immunodeficiencies characterized by impaired immunoglobulin class switching, leading to elevated IgM levels and deficiencies in other antibody isotypes. Among its subtypes, type 2 HIGM is linked to mutations in the activation-induced cytidine deaminase (AICDA) gene mutations (AID deficiency) and can follow autosomal dominant or recessive inheritance patterns, disrupting key processes such as class switch recombination and somatic hypermutation. We report the case of a 17-year-old male diagnosed with autosomal recessive type 2 HIGM, mainly presenting with recurrent sinorespiratory infections, elevated IgM, and decreased other immunoglobulins. Diagnostic workup included serum immunoglobulins, lymphocyte subset analysis by flow cytometry, and genetic testing confirming a pathogenic AICDA mutation. The patient has been managed primarily with immunoglobulin replacement therapy and antibiotic prophylaxis. This case highlights the importance of comprehensive clinical and genetic evaluation for accurate diagnosis and individualized management to improve outcomes and quality of life in patients with HIGM.